VISUAL STUDIES: SCIENTIFIC AND EDUCATIONAL PERSPECTIVES - Pavlova, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2021)
The establishment of Visual Studies area is the result of reflection over the crisis experience not only logocentric one but also over linguistic turns in the field of cultural research, as well as the crisis of images overproduction, which requires other approaches and criteria in production and consumption of video products. The methodological guideline of this research field is not only the extrapolation of research methods of high culture into everyday life, but also the study of the iconic power, including those techniques of visualization of non-visual (for example, not things themselves, but the relationship between things, scientific data, software and etc.), which are offered by contemporary culture as new objects of vision. The visual turn has become the result of a shift in the field of humanities, which captures not only the interest for visual sources of scientific knowledge, but also the specifics of methods and techniques for studying any cultural phenomena, as well as criticism of the absolutization of textual research methods. Writing is defined as a visual practice in its relation to others. In this context, visuality is substantiated as a new cultural phenomenon in the logic of culture de-differentiation (in particular image and text), as well as a separate subject of scientific research. The place of visual culture in the structure of visual studies is defined as a an area that explores first of all not objects that can be seen (especially separate classes of such objects, such as works of fine art), but their connection with “optical media” (F. Kittler) or" visual technology "(N. Mirzoeff), i.e those practices that determine the order of sight. The focus here is on the organization of visual practices in the perspective of technical optical media and video products ratio as an organization order of signifiers. Visual studies emphasize that video production of technical optical media dominates over the bodily parameters of perception (speed and ways of focusing, perception, recollection). The author of the article reflects on the conflicts of problematization of cultural and visual studies in Ukrainian humanities. In this context, the role of "Kyiv worldview and epistemological school" and the methodological meaning of the activity approach developed here are noted. The current state of visual studies and prospects for further development in this area is also defined.